A brief review of C-Dots preparation using top-down and bottom-up approaches - Nur Aini Fauziyah (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
This review paper aimed to reveal several methods that have been used in the preparation of carbon dots (C-Dots). C-Dots were principal to be studied because they have luminous properties that can be used in photocatalyst processes, heavy metal sensors, glowing paints, and nanoparticles for biomedical applications such as bio-tagging. The methods that have been developed were also varied using the two principal approaches, i.e., top-down and bottom-up. Here, we tried to reveal the arc-discharge, laser ablation techniques for top-down approaches, while simple heating methods (simple hydrothermal methods), and microwave for bottom-up. Furthermore, the microwave method was excellent because of the vibration process which caused the carbon chains to undergo rearrangement so that the result was not much reducing the water content in the solution.